2021
DOI: 10.1002/jia2.25820
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated service delivery models among PLHIV in Akwa Ibom and Cross River States, Nigeria during the COVID‐19 pandemic: descriptive analysis of programmatic data

Abstract: IntroductionThe rapid increase in the number of people living with HIV (PLHIV) on antiretroviral therapy (ART) in Akwa Ibom and Cross River states in Nigeria led to overcrowding at clinics. Patients were devolved to receive ART refills through five differentiated service delivery (DSD) models: fast‐track (FT), adolescent refill clubs (ARCs), community pharmacy ART refill programs (CPARPs), community ART refill clubs (CARCs) and community ART refill groups (CARGs) designed to meet the needs of different groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 19 publications
3
40
0
Order By: Relevance
“…Longer refills of 5 to 6 months depending on drug stocks for the CCLAD members have been reported to significantly reduce the rate of frequent visits to the facility and to improve adherence outcomes to ART. 5 Group leaders felt like the model had also improved on ART adherence among the patients enrolled in CCLADS thus improving the quality of life. These findings are in line with those from Dakum’s study that concluded that community ART treatments are associated with adherence and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer refills of 5 to 6 months depending on drug stocks for the CCLAD members have been reported to significantly reduce the rate of frequent visits to the facility and to improve adherence outcomes to ART. 5 Group leaders felt like the model had also improved on ART adherence among the patients enrolled in CCLADS thus improving the quality of life. These findings are in line with those from Dakum’s study that concluded that community ART treatments are associated with adherence and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…3 The World Health Organization (WHO) recommended differentiated HIV service delivery as a novel evidence based strategy to reduce congestion at the facility ART clinic, promote meaningful involvement of People Living with HIV (PLWHIV), and to enhance patients' self-management. 4,5 The differentiated delivery models included Community Client-Led ART Delivery Groups (CCLADs), Community Drug Distribution Points (CDDPs), Facility-Based Groups (FBGs), and Facility-Based Individual Management (FBIM). [6][7][8] In Uganda CCLADs have been implemented as one of the differentiated service delivery (DSD) model since 2017 by the ministry of health.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high interest and urgency statements by the WHO and other international organisations and the knowledge gaps regarding this population, the pace of interventional adolescent HIV research is still slow [2,14]. There is some research with promising findings regarding DSD models for young people in Africa [15][16][17]. A small number of studies on HIV preexposure prophylaxis preferences among young people exist [18,19], but none assessing service or care preferences among young people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…We implemented same-day ART initiation, client navigation services for linkage to ART, structured age-appropriate counseling, support group enrollment, and other peer support services using expert clients. Six Decentralized Drug Distribution (DDD) models-Community Pharmacy ART Refills Program (CPARP), fast track, adolescent refill clubs, community ART refill clubs and groups, and home delivery-were introduced [19,20], and clients received multimonth dispensing (MMD) with refill frequencies of 3, 3-5 and 6-monthly based on national guidance in any of the models [12,19,21]. More adherent clients ultimately received 6 monthly refills.…”
Section: Plos Onementioning
confidence: 99%